2019
DOI: 10.4018/978-1-5225-6164-4.ch008
|View full text |Cite
|
Sign up to set email alerts
|

A Multicriteria Spatiotemporal System for Influenza Epidemic Surveillance

Abstract: Influenza has been a growing concern for the public health decision makers/policy makers. Indeed, they are in need of a real geo-making tool for monitoring and surveillance. The chapter aims to introduce a novel spatiotemporal decision system based on multicriteria ranking method, information geographic system (GIS), and SEIRSW system for public health. The later was designed, implemented, and validated in previous research for influenza risk assessment. The authors highlight the use of PROMETHEE II ranking me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In what follows, we summarize the SIR within SW process without vaccination and with vaccination in a detail pseudo algorithm. The pseudo-algorithms are inspired by the pseudo algorithms used in Younsi et al(2019b): BEGIN 1. Initially, generation of SW network and determination of the list of neighbors of each agent.…”
Section: Sir Compartmental Epidemic Model Within Social Networkmentioning
confidence: 99%
“…In what follows, we summarize the SIR within SW process without vaccination and with vaccination in a detail pseudo algorithm. The pseudo-algorithms are inspired by the pseudo algorithms used in Younsi et al(2019b): BEGIN 1. Initially, generation of SW network and determination of the list of neighbors of each agent.…”
Section: Sir Compartmental Epidemic Model Within Social Networkmentioning
confidence: 99%
“…As shown in Table II, with the exception of Younsi et al (2018), none of the discussed approaches can jointly deal with all the characteristics of seasonal influenza disease, namely (i) the complex nature of seasonal influenza dynamics, (ii) the social structure and activities of individuals, and (iii) the diversity of criteria affecting the seasonal influenza risk assessment. There is also a lack of appropriate decision tools permitting one to monitor and control the spatial and temporal spread of seasonal influenza disease while accounting for the medical, socio-economic, and environmental criteria.…”
Section: Table I Characteristics Of Discussed Approachesmentioning
confidence: 99%
“…Boutkhoum et al (2015Boutkhoum et al ( , 2016 argue that the combination of multicriteria decision analysis with fuzzy sets theory offers an efficient approach to solve complex decision problems and to extract relevant information from S-OLAP results. In a related study, Younsi et al (2018) extended SYDSEP by incorporating the PROMETHEE II (Brans and Mareschal, 2005) ranking method, which improved its analytical capabilities. However, the use of PROMETHEE II in practice necessitates the specification of several preference parameters.…”
Section: Table II Comparative Studymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Gulyaeva et al (2020) reported a model for AI along the Pacific Rim using geospatial methods. In addition, the use of multiple-criteria decision analysis (MCDA) identified potential high-risk areas by monitoring specific factors (Egli et al, 2019;Younsi et al, 2019;Stenkamp-Strahm et al, 2020). All these contribute to a better understanding of the transmission of influenza viruses that could be estimated in great detail by combining geographic, epidemiological and immunological data.…”
Section: Introductionmentioning
confidence: 99%